The Paradox of Hope in Liquid Modernity: Social Transformations and the Value Space of Contemporary Europe - Klose, Ronny (Skhid, 2026)
This article examines Ernst Bloch's radical transformation of hope from its theological to its secular-utopian form through a distinctly socio-philosophical lens. Beginning with an analysis of how Augustinian-Thomistic hope functioned as an ideological mechanism that deferred justice to an otherworldly realm while stabilizing earthly hierarchies, the article traces the crisis of transcendent hope in modernity and identifies Martin Luther's dialectic of the hidden God (deus absconditus) as the crucial conceptual bridge to Bloch's philosophy. Bloch's ontology of the Not-Yet relocates hope within immanent, material processes, distinguishing between anticipatory "waking dreams" (Tagträume) that orient toward real possibilities and compensatory fantasies that defer transformation. The article explores Bloch's concept of concrete utopia – grounded in actual historical tendencies through docta spes (educated hope) – and its influence on liberation theology and social movements of the 1960s-70s. Critical examination reveals three fundamental challenges: the fragmentation of the revolutionary subject after 1989, the totalitarian dangers when utopian hope hardens into ideology, and the theodicy problem of sustaining hope without metaphysical guarantees. Contemporary analysis demonstrates how late capitalism colonizes futurity itself, yet new movements – from climate justice to solidarity economies – practice prefigurative politics that embody Blochian hope as democratic praxis. The article argues that Bloch is not simply overcoming but radically inheriting Christian eschatology's messianic structure, relocating it from transcendence to immanence, from divine grace to collective human agency, creating a hope adequate to our post-religious yet deeply utopian-needing age.